Expression and alteration of BKCa channels in the sphincter of Oddi's from rabbits with hypercholesterolemia. Issue 3 (4th May 2017) - Feng, Dan; Nan, Haiyan; Wang, Wen; Yan, Linfeng; Du, Pang; Zuo, Lin; Zhang, Kun; Zhao, Minggao; Cui, Guangbin
ABSTRACT: This study aimed to investigate the expression and function of BKCa channels in the Sphincter of Oddi (SO) in a rabbit model of hypercholesterolemia (HC). New Zealand white rabbits were randomly divided into 2 groups: the control group was fed standard chow ( n = 18) whereas the high-cholesterol group was fed cholesterol-enriched chow containing 1.5% cholesterol ( n = 18). The serum cholesterol level was significantly greater in the HC groups than in the control group, but there was no significant difference in body weight between the control and HC groups. Although the total protein expression of BKCa α- and β1 -subunit was not significantly different between the control and HC groups, the Tyr-phosphorylation of BKCa α-subunit was significantly decreased in the HC group than in the control group. In addition, hypercholesterolemia significantly increased Acetylcholine (ACh)-induced contraction of the SO rings. Pretreatment with 30 μM NS1619, a BKCa channel agonist, significantly reduced ACh-induced contraction of the SO rings in HC rabbits. Moreover, pretreatment with 100 μM Na3 OV4, a protein tyrosine phosphatase inhibitor, significantly reduced ACh-induced contraction of the SO rings in HC rabbits, whereas it significantly increased upon pretreating with 10 μM Genistein, a tyrosine kinase inhibitor. Whole-cell patch clamp recordings showed that BKCa current density was significantly lower in SOSMCs from HC group than that from control group. Our findings suggest that hypercholesterolemia-induced downregulation of BKCa channel, and Tyr-phosphorylation of BKCa α-subunit may contribute to the hyperresponsiveness of the SO ring in HC rabbits.